2022
DOI: 10.1177/10499091221115732
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Usual Palliative Care Consultation in the Intensive Care Unit

Abstract: Objectives Palliative Medicine involvement in MICU patients have improved length of stay and mortality, but with varying effects on specific patient decision outcomes, such as, advance care planning. These studies have utilized Palliative Medicine later in the hospital or ICU course, with some evidence showing that earlier involvement resulted in better results. The purpose of this study was to evaluate the benefits of early (within 24 hours) palliative care consultation in medical ICU (MICU) patients to clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…10 Similarly, the study by Helgeson et al provided evidence that early palliative care counseling, within 24 hours of admission to the ICU, improved patient satisfaction with significant benefits. 11 Although the evidence suggests that early palliative care involvement during severe illness is essential. Further studies are needed to determine its impact on ICU patients with particular emphasis on outcomes such as quality of life based on patients' perceptions rather than the perceptions of their families.…”
Section: Impact On Quality Of Life In the Icumentioning
confidence: 99%
See 1 more Smart Citation
“…10 Similarly, the study by Helgeson et al provided evidence that early palliative care counseling, within 24 hours of admission to the ICU, improved patient satisfaction with significant benefits. 11 Although the evidence suggests that early palliative care involvement during severe illness is essential. Further studies are needed to determine its impact on ICU patients with particular emphasis on outcomes such as quality of life based on patients' perceptions rather than the perceptions of their families.…”
Section: Impact On Quality Of Life In the Icumentioning
confidence: 99%
“…In several studies, the provision of palliative care in the ICU has been associated with increased rates of advance care planning, increased use of palliative care facilities, decreased length of stay, and decreased use of non-beneficial life-sustaining treatments. [11][12][13][14][15][16][17] In addition, the study by Ma et al found that routine palliative care can positively influence the care of critically ill patients. In contrast, early palliative care counseling was posihttps://ejournals.epublishing.ekt.gr/index.php/HealthResJ tively associated with more excellent transitions to do-notresuscitate/non-intubation, hospitalization in palliative care facilities, and reduced use of healthcare resources pre-ICU and post-ICU.…”
Section: Reducing the Use Of Icu At The End Of Lifementioning
confidence: 99%
“…Four studies [38,48,51,57] included multiple diseases, three included both cancer and noncancer conditions [38,51,57], and one included both CHF and COPD [48]. Three studies stated general chronic/advanced noncancer populations [46,53,55], and one included intensive care unit (ICU) populations [40].…”
Section: Participantsmentioning
confidence: 99%
“…All eleven models were composed of multi-components of palliative care intervention, such as symptom management, self-management education of disease, end-of-life discussions, case conferences, documentation, regular home visits, or a telephone hotline. Seven studies [35,38,40,[43][44][45]47] provided inpatient care and six [36,37,39,41,42,46] implemented outpatient palliative care services. Inpatient palliative care services in seven studies were developed based on the standard referral process of the hospital palliative care team or developed for the trial.…”
Section: Intervention and Controlmentioning
confidence: 99%
See 1 more Smart Citation